Improving Students' Reading Comprehension of Recount Text with the Use of Language Learning Application - Dwi Ima Herminingsih; Latifatul Isro'iyah; Sindhu Rhineksha Mukti (International Journal of Education and Digital Learning (IJEDL), 2024)
This study aims to assess the impact of utilizing the Beelinguapp program on the reading comprehension skills of second semester students in the Faculty of Social and Political Science, specifically in the area of understanding recount texts. This study utilizes a quantitative approach and follows a pre-experimental design with a one-group pre-test-post-test design. The study population consists of students enrolled in the Faculty of Social and Political Science. The sampling technique use random sampling to select a sample of 31 students in the second semester class. Data collection is conducted through the use of pretest and posttest measures. The Shapiro-Wilk normalcy test is employed for doing normality testing. The Wilcoxon Signed Ranks Test is a non-parametric statistical method employed for data analysis in this research. According to the data, the average score in the pretest and posttest increased from 76.87 to 86.97. The normalcy test indicates that the pretest has a significance value of 0.000, whereas the posttest has a significance value of 0.002. The significance value analysis indicates that the dataset obtained from 31 students does not follow a normal distribution, as evidenced by a significance value of less than 0.05. The analysis results from the test statistic output show that the asymp. sig. (2-tailed) value is 0.000 < 0.05. A significance value smaller than 0.05 indicates that there is an average difference that makes Ha accepted and Ho rejected. It can be concluded that there is a significant effect of the Beelinguapp application to enhance the reading comprehension of recount text of eighth-class students at Faculty of Social and Politics Science. The researcher aspires for this study to serve as a research reference for upcoming research.